Unified treatment of bound-state and scattering problems - Adhikari, Sadhan K.; Tomio, Lauro [UNESP] (American Physical Society (APS), 1988)
The iteration-subtraction method for the unified treatment of bound-state and scattering problems is compared and contrasted with a similar method for the two-body bound-state problem via nonsingular scattering equations developed recently. We also compare another recent method for solving bound-state problems with the iteration-subtraction method. © 1988 The American Physical Society.